Rapid and Complete Surface Modification with Strain‐Promoted Oxidation‐Controlled Cyclooctyne‐1, 2‐Quinone Cycloaddition (SPOCQ). Issue 12 (15th February 2017) - Sen, Rickdeb; Escorihuela, Jorge; van Delft, Floris; Zuilhof, Han
Abstract: Strain‐promoted oxidation‐controlled cyclooctyne‐1, 2‐quinone cycloaddition (SPOCQ) between functionalized bicyclo[6.1.0]non‐4‐yne (BCN) and surface‐bound quinones revealed an unprecedented 100 % conjugation efficiency. In addition, monitoring by direct analysis in real time mass spectrometry (DART‐MS) revealed the underlying kinetics and activation parameters of this immobilization process in dependence on its microenvironment. Abstract : Throwing DARTs at a surface : The strain‐promoted oxidation‐controlled cyclooctyne‐1, 2‐quinone cycloaddition (SPOCQ) between bicyclo[6.1.0]nonyne (BCN) and a surface‐bound quinone revealed an unprecedented 100 % conjugation efficiency.